The Performance of Brass Electrode on Material Removal for Aluminium Composite in EDM Die-Sinking - Md Ali, Mohd Amran; Laily, Suraya; Fatin, Aisyah; Hussein, Nur Izan Syahriah; Muhamad, Mohd Razali; Manshoor, Bukhari; Mohd Amri, Lajis; RAJA ABDULLAH, RAJA IZAMSHAH; Abu Bakar, Mohd Hadzley; Taufik, Roni Sahroni (Trans Tech Publications, Switzerland, 2014)
This paper investigates the performance of brass electrode on the removal of aluminium alloys LM6 (Al-Sil2) in an electrical discharge machining (EDM) die-sinking. The machining parameters such as pulse-on time, pulse-off time and peak current were selected to find the responses on the material characteristics such as material removal rate (MRR), electrode wear rate (EWR) and surface roughness (Ra). Brass with diameter of 10mm was chosen as an electrode. Orthogonal array of Taguchi method was used to develop experimental matrix and to optimize the MRR, EWR and Ra. It is found that the current is the most significantly affected the MRR, EWR and Ra while pulse on time, pulse off time and voltage are less significant factor that affected the responses. Percentage optimum value of MRR increases to 3.99%, however EWR and Ra reduce to 3.10% and 2.48% respectively. Thus, it shows that brass having capability to cut aluminium alloys LM6.